SPORTS IN SHORT (Knight Ridder Tribune Business News, 2006)
May 10--LOWBALL EVENT The following teams finished with top scores in the Thursday lowball event at Foxwood Country Club: Terry Menard, Tommy Menard, Fred Heiler, Jesse Dennis 12; John Wacholz, David Hinnant, Claude Stiles, Mike Hinnant, Bill Chandler 11; Terry Thomas, Faye Thomas, Archie Perez, Tom Sannino 9; David Gansel, Jimmy Johnson, Robert Reed, Charlie Peele 9; Gene Kester, Dave Smith, Fred Scheider, Jerry Devoy 9. Next Thursday lowball is May 11 at 8 a.m. Call 682-2012.